The Plasminogen Content of Thrombi - Ogston, D; Ogston, C. M; Fullerton, H. W (Thrombosis and Haemostasis, 1966)
1. The plasminogen content of serum and plasma does not differ. The serum remaining after the production of an in vitro artificial thrombus has a plasminogen content similar to the original plasma. Direct measurement of the plasminogen content of artificial thrombi confirms that little plasminogen is adsorbed onto fibrin during the process of clotting.2. The lysis of pre-formed artificial thrombi by urokinase is substantially increased in the presence of plasma. This is not due to free plasmin in the medium surrounding the thrombus.3. Partially purified plasminogen is adsorbed onto artificial thrombi endowing them with the capacity to lyse on the addition of urokinase. In contrast plasminogen from plasma or serum is not adsorbed onto thrombi.4. We suggest that the lysis of a thrombus results from diffusion of circulating plasminogen into the thrombus and its interaction with activator on the surface of the fibrin fibrils with consequent plasmin formation.